2018
DOI: 10.1103/physrevx.8.031081
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of a Coherent Lattice Transformation into a High-Symmetry Phase

Abstract: †These authors contributed equally to this work Excursions far from their equilibrium structures can bring crystalline solids through collective transformations including transitions into new phases that may be transient or long-lived. Direct spectroscopic observation of far-from-equilibrium rearrangements provides fundamental mechanistic insight into chemical and structural transformations, and a potential route to practical applications, including ultrafast optical control over material structure and propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
(71 reference statements)
1
28
0
Order By: Relevance
“…[46,47] These works triggered a vivid discussion about ultrafast transient solid-solid phase transitions, which were further investigated by numerous groups, reporting evidence for nonthermal melting, [48] transient formation of a high-symmetry solid phase in ref. [49]. However, these works also showed that such transient states are short-lived (tens of picosecond time scale), require femtosecond excitation to be triggered, and are accompanied by electron-phonon relaxation and thermal diffusion in longer time scales.…”
Section: Understanding Switching Dynamics In Bi Metasurfaces: Tuning the On-statementioning
confidence: 99%
“…[46,47] These works triggered a vivid discussion about ultrafast transient solid-solid phase transitions, which were further investigated by numerous groups, reporting evidence for nonthermal melting, [48] transient formation of a high-symmetry solid phase in ref. [49]. However, these works also showed that such transient states are short-lived (tens of picosecond time scale), require femtosecond excitation to be triggered, and are accompanied by electron-phonon relaxation and thermal diffusion in longer time scales.…”
Section: Understanding Switching Dynamics In Bi Metasurfaces: Tuning the On-statementioning
confidence: 99%
“…A 4f imaging systems was used to relay the signal and reference grids onto a CCD (Hamamatsu Orca-ER). These grids were then combined, binned and unfolded to generate a pump-probe transient reflectivity trace measured in each laser shot [18,30].…”
Section: Single-shot Nir Transient Reflectivitymentioning
confidence: 99%
“…Singleshot time-resolved spectroscopy techniques, on the other hand, can capture, with a single pump laser shot, the real-time dynamical evolution of slowly reversible and irreversible processes. [12,18,19] Single-shot measurements thereby can offer unique mechanistic insights into the formation of metastable hidden phases.…”
Section: Introductionmentioning
confidence: 99%
“…iffusionless solid-to-solid transitions (martensitic transition) have been widely observed in both hard materials, such as metals, alloys, and ceramics [1][2][3][4][5][6][7][8][9][10] , and soft-matter systems, such as protein solutions and colloidal suspensions [11][12][13][14] . Despite the variety of these systems with various softness and symmetry [4][5][6][7][8][9][10][11][12][13][14] , one common intriguing feature is the formation of rich microstructures via complex nucleation and growth pathways. Nuclei formation has so far been believed to be athermal because immense strain energy is required to overcome a high barrier, which is the case for the steel's martensitic transition.…”
mentioning
confidence: 99%